A STUDY OF MARKETING MIX STRATEGY OF PINASUNGKULAN AND BERSEHATI TRADITIONAL MARKET TRADERS IN MANADO CITY - Salomonsz, Gabriel Victory (FEB Universitas Sam Ratulangi Manado, 2016)
The traditional market is a place for sellers and buyers meet to make a transaction â€“ buying and selling â€“ which is usually with a unique way like a bargain. The traditional market traders have a variety problems which are the competition with the others traditional market traders and competition with the modern market. Traditional market traders as sembako traders, vegetables, and meats should have a marketing strategy to solving this problems. In this study, the authors want to show the issue, 1) How are the marketing mix strategy of the traditional market traders, the sembako traders, vegetables and meats to face the competition; 2) What are the success factors of traditional market traders to complete the marketing mix.Â The author uses descriptive type and using qualitative methods. The location of this research in Pinasungkulan traditional market and Bersehati traditional market.To face and take control these problems, the traditional market traders in Pinasungkulan traditional market and Bersehati traditional market must create the quality of the product, choose the strategic location, determine the affordable price and keep the uniqueness of promotion, to increase the selling. Keywords: marketing mix strategy, traditional market, traders